The effects of lower crustal strength and preexisting midcrustal shear zones on the formation of continental core complexes and low‐angle normal faults. Issue 9 (29th September 2016) - Wu, Guangliang; Lavier, Luc L.
Abstract: To investigate the formation of core complexes and low‐angle normal faults, we devise thermomechanical simulations on a simplified wedge‐like orogenic hinterland that has initial topography, Moho relief, and a preexisting midcrustal shear zone that can accommodate shear at very low angles (<20°). We mainly vary the strength of the lower crust and the frictional strength of the preexisting midcrustal shear zone. We find that the strength of the lower crust and the existence and strength of a preexisting shear zone significantly affect the formation and evolution of core complexes. With increasing lower crustal strength, we recognize varying extensional features with decreasing exhumation rate: these are characterized by bivergent metamorphic massifs, classic Cordilleran metamorphic core complexes, multiple consecutive core complexes (or boudinage structures), and a flexural core complex underlined by a large subsurface low‐angle detachment fault with a small convex curvature. Topographic loading and mantle buoyancy forces, together with divergent boundaries, drive a regional lower crustal flow that leads to the exhumation of the lower crust where intensive upper crustal faulting induces strong unloading. The detachment fault is a decoupling zone that accommodates large displacement and accumulates sustained shear strain at very low angle between upper and lower crust. Though the regional stress is largely Andersonian, we find non‐Andersonian stress in regions adjacent to the preexisting shear zone and those with high topographic gradient. Our new models provide a view that is generally consistent with geological and geophysical observations on how core complexes form and evolve. Key Points: The origin of core complexes is proposed based on numerical models The new models are consistent with regional geology and geophysics in the U.S. Cordillera and the Aegean Tectonic significance and implications of core complexes are discussed in the context of U.S. Cordillera and the Aegean